Optimal mechanism in governmental project screening: A theory of Kornai's soft budget constraint - Chong-En Bai; Yijiang Wang (Journal of Government and Economics (JGE), 2022)
Soft budget constraint refers to the phenomenon that money losing inefficient projects keep on getting subsidies and operating. It was first phrased and analyzed by the late Hungarian economist Janos Kornai when he studied former socialist economies and by now, economists generally have agreed that soft budget constraint also exists extensively in market economies. As an important area of research in government and economics, existing explanations of soft budget have focused on the government's lack of commitment to terminate inefficient investment projects. In this paper, we propose a new theory in which soft budget constraint is an optimal governmental mechanism to induce greater effort in project selection. The idea is that if a manager (banker) selects a bad project, he has to keep on subsidizing it and lose more. Anticipating this, soft budget constraint makes the manager work hard to avoid choosing bad projects. Our theory sheds light on research in government and economics from the perspective of mechanism design.
Keywords: D23; 330; Soft budget constraint; Agency; Ex post inefficiency